نظام مساعدة طارئة باستخدام الدرون - Karaki, Nawal; Daghamin, Suzan; Albaba, Mohammad (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2022)
تُعّد حوادث السير من أبرز األسباب المؤ ِسفة التي تحصد عشرات األرواح من البشر يومياً حول العالم، إلى جانب وقوع العديد من الجرحى، واألضرار الجسيمة التي تلحق بوسيلة النقل، وذلك رغم تزايد حمالت التوعية في أسابيع المرور العالمية، وعلى مدار العام أيضا باب حوادث السير، وفي هذا المشروع سيكون التركيز على الحوادث المرورية التي تحصل ً، وتتعدد أس بين المركبات . ففي كثير من الحاالت ما يواجه هذا الشخص الصعوبات في استخدام هاتفه وتدبر أموره، نتيجة االرتباك الناجم عن سلمة الحادث، أو لريما عدم مقدرته على القيام بإجراء مكالماته بشكل يدوي. ومن هنا تأتي أهمية مشروعنا ، والتي تتمثل ب تطوير نظام يقوم بمهام مشابهة للتي سيقوم بها هذا الشخص، ولكن بشكل آلي کامل عبر سلسلة من الخطوات المتزامنة التالية: 1 .إعطاء إنذار لبعض الوقت – يحتدم الشخص بالبرنامج مسبقاً -، في حال اختالف مفاجئ في سرعة الشخص )تغير في التسارع( الناجم عن تصادم المركبات أو السقوط عن المرتفعات على سبيل المثال. 2 .في حال تمكن الشخص من الوصول لهاتفه وتدبر أموره، فهو أمام خيارين: • إما إغالق اإلنذار ، وتدير أموره بشكل يدوي. • أو القيام بالخطوات الالحقة، واختصار الوقت المحدد لإلنذار بالنقطة رقم.(1( 3 .وإذا لم يكن بمقدور الشخص الوصول لهاتفه، وبعد انتهاء الوقت المحدد لإلنذار يقوم البرنامج بإرسال رسالة تنبيه للسيرفر الخاص بمركز الطوارئ مفادها طلب المساعدة مع اإلشارة لموقع الشخص الجغرافي ومعلوماته الشخصية المخزنة مسبقا ، مع قراءة المعلومات الحيوية األولية للمصاب من خالل التطبيق المرتبط بالساعة الذكية. ً 4 .ارسال الدرون المحملة بحقيبة اإلسعافات األولية للمكان لتزويد المصاب بالمساعدات األولية وإننا بهذا النظام نكون قد حققنا عدة أهداف، أهمها تلبية نداء االستغاثة وتسريع عملية التبليغ عن وقوع الحادث لهذا ، كما أسلفنا سابقاً الشخص في أحلك حاالته كغيابه عن الوعي أو إصابته بالعجز ويمكن تطويره بالكفاءة الالزمة الستخدامه من قبل المواطنين للعمل كنظام أولي يقوم ب إعالم مركز الطوارئ عن وقوع الحادث وبالتالي يمكنه الحفاظ على السالمة الجسمية والتقليل من عدد الوفيات . Traffic accidents are one of the most unfortunate reasons that claim dozens of lives every day around the world, in addition to the occurrence of many injuries and serious damage to the means of transportation, despite the increase in awareness campaigns in global traffic weeks, and throughout the year as well, and the causes of traffic accidents are many. And in this project, the focus will be on traffic accidents that occur between vehicles. In many cases, this person faces difficulties in using his phone and managing his affairs, as a result of the confusion caused by the safety of the accident, or his inability to make his calls manually. Here comes the importance of our project, which is to develop a system that performs tasks similar to what this person will perform, but completely automatically through a series of the following simultaneous steps: 1. Giving a warning for some time - the person raging with the program in advance - in the event of a sudden difference in the person’s speed (change in acceleration) caused by collisions of vehicles or falling from heights, for example. 2. If the person manages to reach his phone and manage his affairs, He has two options: • Either close the alarm, and manage its affairs manually. • Or take the subsequent steps, and shorten the time specified for the warning in point No. (1). 3. If the person is not able to reach his phone, and after the specified time for the warning expires, the program sends an alert message to the private server at the emergency center, it is a request for help with reference to the person’s geographical location and his previously stored personal information, with reading the initial vital information of the injured through the application linked to the smart watch. 4. Sending the drones loaded with the first aid bag to the place to provide the injured with first aid. 8 | P a g e With this system, we will have achieved several goals, the most important of which is responding to the distress call and speeding up the process of reporting the accident to this person in his darkest condition, such as unconsciousness or incapacitation, as mentioned previously. It can be developed with the necessary efficiency to be used by citizens to act as a primary system that informs the emergency center about the occurrence of the accident and thus can maintain physical safety and reduce the number of deaths
Drone emergency assistance system
no of pages 68, هندسة حاسوب 5/2022
Keywords: انظمة الدرون